The assessment of a legislator’s actions under the provisions of the Criminal Procedure Code concerning compensation for unjustifiable use of coercive measures, with particular emphasis on seizure of property - Ostrzycka, Martyna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2016)
Recently, amendments to the Criminal Procedure Code have been made with unusual frequency. On 1 July 2015, the provisions which made a fundamental remodeling of the criminal procedure came into force. These included innovative regulations for the possibility of applying for compensation from the State Treasury for unjustifiable use of coercive measures, including seizure of property. Although the implementation of these provisions was consistent with the standpoint of the majority of the doctrine, they were only in force for less than ten months. In the motives of the bill, which had removed them from the Code, there was actually no justification for such actions of the legislator. Because they were in force for such a short duration, there is no possibility of assessing their functioning.Such actions of the legislator deserve the highest criticism, because there is an undeniable need to protect persons against whom coercive measures, including seizure of property, were unjustifiably applied.